Studi Kasus Kualitas Pengelasan Pada Material A694 F65 Overlay Inconel 625 Claded Menggunakan Metode Kombinasi Gtaw & Smaw - Sugondo, Ebeng; Purba, Adi Syahputra; Kms M Avrieldi; Ismiyatun Nurjannah (Politeknik Negeri Batam, 2025)
Welding is a method of connecting metal that involves melting a portion of the parent and filler metals until they are liquid enough to fuse. Nowadays, welding is becoming more and more common, particularly in the oil and gas sector. Combining GTAW with SMAW techniques is one of them. Because it can create robust and corrosion-resistant joints, the oil and gas industry frequently uses the combination of GTAW and SMAW welding techniques. The welding procedure on ASTM A694/F65 material covered with Inconel 625 will be covered in this study. While Inconel 625 is resistant to corrosion and stress cracking, A694/F65 steel will offer toughness for applications with low temperature field circumstances. The benefits of the various welding techniques are strategically integrated by this combination of welding procedures. While SMAW delivers great mechanical strength and filling efficiency for the fill to cap weld portions, GTAW will offer superior penetration and surface cleanliness on the root weld. The results of the tests, which included visual inspection, Magnetic Particle Inspection (MPI), and Ultrasonic Testing (UT), demonstrated that no evidence of serious flaws exceeding the acceptance criteria of the cited standards AWS D1.1:2025 for MPI and ASME Section VIII Div. 1 Appendix 12 for UT was discovered. It is anticipated that the study will serve as a guide for the welding procedure on gas and oil pipes.